. Analysis of CXCL12 and S100A12 levels in peripheral blood and synovial fluid and their correlation with severity in patients with knee osteoarthritis: CXCL12 and S100A12 - Ye, Yili (Journal of Medical Biochemistry, 2024)
Abstract: To investigate the expression of CXCL12 and S100A12 in peripheral blood (PB) and synovial fluid (SF) of patients with knee osteoarthritis (OS) and to analyze the correlation between them and the severity of knee OS. 60 patients with kneeOS treated in our hospital from January 2020 to December 2022 were selected as the experimental group, and 60 healthy knee joints with similar age were selected as the control group. The fasting venous blood of 120 subjects was drawn in the early morning, and the SF was extracted during joint operation or sodium hyaluronate injection. Put the collected PB and SF in the refrigerator at-80℃. The levels of CXCL12 and S100A12 in PB and SF were detected by enzyme linked immunosorbent assay (Elisa). The correlation between the levels of CXCL12 and S100A12 in PB and SF and Kmurl L grade and WOMAC score. The levels of CXCL12 and S100A12 in PB and SF in the observation group were raised than those in the control group. There were significant differences in the levels of CXCL12 and S100A12 in PB and SF in the experimental group. The higher the Kmurl grade of knee OS, the higher the concentration of CXCL12 and S100A12 in PB and SF. The levels of CXCL12 and S100A12 in PB of knee OS were positively correlated with WOMAC score (r = 0.767, 0.521 respectively, P < 0.05), see figure 1. The levels of CXCL12 and S100A12 in SF of knee OS were positively correlated with WOMAC score (r = 0.663, 0.357 respectively, P < 0.05). The levels of CXCL12 and S100A12 in PB and SF are positively correlated with the severity of knee OS. The levels of CXCL12 and S100A12 in PB and SF can provide basis for the evaluation and prognosis of knee OS.
Keywords: knee osteoarthritis, CXCL12, S100A12, correlation